2021
DOI: 10.4103/ijnm.ijnm_134_20
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Standardized Uptake Value Threshold for Auto contouring of Gross Tumor Volume using Positron Emission Tomography/Computed Tomography in Patients with Operable Nonsmall-Cell Lung Cancer

Abstract: Purpose: Incorporating 18 F-fluorodeoxyglucose positron emission tomography-computed tomography ( 18 F-FDG-PET/CT) for gross tumor volume (GTV) delineation is challenging due to varying tumor edge based on the set threshold of the standardized uptake value (SUV). This study aims to determine an optimal SUV threshold that correlates best with the pathological tumor size. Materials and Methods: From January 2013 to Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Besides, in a prospective study by Tibdewal et al including 37 patients with operable NSCLC, MTV delineated with an absolute threshold of SUV of 4.0 correlated best with postoperative pathological tumor size. 29 More recently, the fixed absolute threshold of SUV>4.0 has also been designated as the method of choice in a prospective study by Driessen et al evaluating MTV delineation on lymphoma, requiring the least manual adaptation, allowing a high reproducibility and being observer independent. 30 According to the authors, this threshold should now be used in further studies to reach a consensus standard method.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in a prospective study by Tibdewal et al including 37 patients with operable NSCLC, MTV delineated with an absolute threshold of SUV of 4.0 correlated best with postoperative pathological tumor size. 29 More recently, the fixed absolute threshold of SUV>4.0 has also been designated as the method of choice in a prospective study by Driessen et al evaluating MTV delineation on lymphoma, requiring the least manual adaptation, allowing a high reproducibility and being observer independent. 30 According to the authors, this threshold should now be used in further studies to reach a consensus standard method.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies incorporating PET into treatment planning have been reported (Kiffer et al, 1998). Some have arbitrarily advocated the FDG-avid volume as the region encompassed by the 50% intensity level relative to the tumor maximum intensity (Arriagada et al, 1991;Le Chevalier et al, 1994), whereas Bradley et al, (2004) and TMH data (Tibdewal et al, 2021) employed the 40% intensity level. Paulino and Johnstone (2004) suggested in an editorial autocontouring all areas with a standardized uptake value (SUV) of 2.5.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor segmentation was executed using AccuContour software (version 3.2, Manteia Medical Technologies Co., Ltd., Xiamen, China). Two experienced nuclear medicine physicians employed a threshold of 40% of the maximum standardized uptake value (SUVmax) to delineate the gross tumor volume (GTV) on PET images, reaching a consensus without prior knowledge of the pathology [ 18 , 19 ]. Concurrently, the contours of the GTV on CT slices were outlined based on the integration of PET and anatomical data from the CT images.…”
Section: Methodsmentioning
confidence: 99%